Engineering Solutions to Optimise the Design of Carbon-Neutral Tall Office Buildings - Pitman, Mark; King, Andrew (Society for Sustainability & Environmental Engineering, 2009)
Energy efficiency differs by building use and type as well as prevailing climatic conditions. This study examines the energy efficiency of tall office buildings in a Mediterranean climate by investigating the energy balance for a typical level (or storey) of a building that may be of arbitrary form or style. The resulting generalized model gives new insight to the engineering challenges facing the design of carbon-neutral buildings and has the potential for widespread use as a design tool that can be integrated with the architectural and engineering design of building projects in any climate region. In order to efficiently quantify the effects of a large number of parametric permutations that characterise different building forms and systems mathematical modelling and simulation are adopted to construct a virtual prototype for each building and its associated systems. Energy modelling is used to calculate the building-energy loads resulting from solar gains and occupancy, while computational fluid dynamics (CFD) is used to assess detailed air flow within the building as well as external wind patterns and pressure profiles which may be harnessed to provide supplementary energy to the building. Parameters assessed for their impact on the energy consumption for each typical level include: the floor-plate geometry; façade construction; glazing positioning; fixed and operable shading devices; various Heating Ventilation and Air-Conditioning (HVAC) systems; building-management profiles and occupant comfort bands. The results of the study indicate that, through the appropriate design and optimisation of these parameters, the cross-over point where energy consumption for a given floor area balances the harvestable renewable energy for each typical level may be maximized towards a theoretical limit. The results of these investigations may be used to optimise the energy and carbon-neutral design of base-buildings while maintaining occupancy usability ratings such as availability of daylight, temperature and comfort bands within acceptable limits.